2022
DOI: 10.1007/s11747-022-00862-x
|View full text |Cite
|
Sign up to set email alerts
|

Robots do not judge: service robots can alleviate embarrassment in service encounters

Abstract: Although robots are increasingly used in service provision, research cautions that consumers are reluctant to accept service robots. Five lab, field, and online studies reveal an important boundary condition to earlier work and demonstrate that consumers perceive robots less negatively when human social presence is the source of discomfort. We show that consumers feel less judged by a robot (vs. a human) when having to engage in an embarrassing service encounter, such as when acquiring medication to treat a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(34 citation statements)
references
References 65 publications
3
31
0
Order By: Relevance
“…Building on social cognitive theory (Fiske et al, 2002(Fiske et al, , 2007, we provide evidence for the role of warmth (vs competence) in reducing disconfirmed expectations. This provides a theoretically informed route to lowering possible customers' negative responses towards the service and responds to the recent call posed by Holthöwer and van Doorn (2022) to show how robots' negative effects can be attenuated.…”
Section: Theoretical Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Building on social cognitive theory (Fiske et al, 2002(Fiske et al, , 2007, we provide evidence for the role of warmth (vs competence) in reducing disconfirmed expectations. This provides a theoretically informed route to lowering possible customers' negative responses towards the service and responds to the recent call posed by Holthöwer and van Doorn (2022) to show how robots' negative effects can be attenuated.…”
Section: Theoretical Contributionsmentioning
confidence: 99%
“…In particular, the optimal level of EJM 57,4 humanoid appearance for service robots remains unexplored (Wirtz et al, 2018;Belanche et al, 2020a). Moreover, theoretical and empirical exploration is imperative to uncover how robots' negative effects can be attenuated or avoided (Holthöwer and van Doorn, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Although consumers are increasingly reliant on digital service encounters, they do not always readily accept technological service providers; thus, the use of such technologies can evoke skepticism and trigger negative feelings (Holthöwer & van Doorn, 2022; Mozafari et al, 2021). Skepticism refers to a person's tendency to doubt, not believe, or question (Boush et al, 1994; Foreh & Grier, 2003).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Uchida et al (2017) compared a robot and a human mental health counselor and found that the extent of personal disclosure to the counselor depends on the perceived sensitivity of the disclosed topic. As another example, Pitardi et al (2022) and Holthöwer and van Doorn (2022) found that reduced perceptions of agency from a robot (vs. human) service provider could make customers feel less embarrassed during potentially embarrassing service encounters (e.g., embarrassing medical treatments). This work focused on anticipated embarrassment and suggested the importance of examining various contextual factors that may further influence self-disclosure.…”
Section: Previous Research On Self-disclosurementioning
confidence: 99%